OPTIMALISASI PERAN PEMERINTAH DAN BPJS KESEHATAN DALAM PENANGANAN STUNTING DI KABUPATEN MERAUKE - Prasetya, Muhammad Novan; Syahruddin, Syahruddin; Haris, Umiyati; Adam, Aenal Fuad (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2024)
Stunting is a troubling social problem in Merauke Regency, South Papua, the Head of Merauke Regency Health Office stated that the number of stunting has increased from 2021 to 2022, through the Electronic Application for Community-Based Nutrition Recording and Reporting (E-ppgbm), as of August 2022 reported by all health centers in Merauke Regency, there were 2,015 stunting toddlers. The purpose of this research is to analyze the problem of stunting and find steps to handle and prevent stunting in Merauke. This research method uses descriptive qualitative. From the above problems, to overcome stunting in Merauke, there are three ways taken by the Merauke government. First, BPJS provides access to quality health services for children who are vulnerable to stunting. Second, There is a Merauke government policy to formulate stunting handling and increase public awareness about balanced nutrition and healthy lifestyles. Third, Optimizing the role of BPJS Health and the government can contribute to achieving the welfare of the 2045 golden generation in Merauke Regency.